APPROACHES TO PERFORMANCE MANAGEMENT IN MODERN ORGANISATIONS - Loso Judijanto; Benediktus Rolando; Al-Amin (CV. Adiba Aisha Amira, 2024)
Performance management in the context of modern organisations requires an approach that adapts to the fast-changing business environment and evolving employee expectations. Recent approaches emphasise the importance of continuous dialogue, the use of technology for proper analysis of performance data, and the building of a supportive work environment to optimise employee potential. By integrating communicative techniques, data analytics, and appropriate individual development strategies, performance management becomes more than just an evaluation; it becomes a catalyst for individual and organisational growth. This modern approach not only improves overall performance but also promotes continuous adaptation and innovation, paving the way for the achievement of strategic goals and business continuity in a dynamic environment. This represents a shift from the traditional paradigm towards a more holistic practice, where performance management is seen as central to organisational development and employee satisfaction.